Halal and Haram in the Qur’an and Hadith: The Theological Foundations of Halal Certification in Indonesia - Warto Ahmad Saifuddin (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2025)
This article examines the theological construction of halal and haram in the Qur’an and Hadith as the normative, epistemic, and operational foundation of the halal certification system in Indonesia. The study employs a qualitative approach with a thematic exegesis (maudhu‘i) design applied to primary texts, combined with content analysis of regulations and standards. Primary data include Qur’anic verses on halalan tayyiban, typologies of prohibition, and hadiths concerning shubhat as well as legal maxims (qawa‘id fiqhiyyah), while secondary data consist of Law No. 33/2014, SNI 99001:2022, HAS 23000, and reputable scholarly literature. The analysis identifies four operational theological pillars: the cumulative principle of halalan tayyiban; typologies of prohibition based on substance (li ‘aynihi), process (li ghairihi), and harm; legal maxims as risk management principles (al-yaqin la yazulu bi al-shakk, la darar wa la dirar, sadd al-dhara’i); and maqasid al-shari‘ah as governance objectives. These pillars are directly aligned with the clauses of the Halal Management System SNI 99001:2022 and the BPJPH–LPH–MUI mechanism. The findings present a replicable framework of revelation–fiqh–standards integration, propose a Halal Critical Control Points (HCCP) model compatible with HACCP, and emphasize the role of digital traceability in upholding the principle of certainty (al-yaqin). The practical implications include strengthening the integrity of the halal supply chain, enhancing the accountability of fatwa decisions, and improving the competitiveness of the national halal industry.